Preliminary Results of the Implementation of a Patient Blood Management Protocol in the Surgical Correction of Pediatric Scoliosis - Ferreira, Ana Margarida; Nóbrega, Sónia; Alves, Marta; Virella, Daniel; Ramos, Sara (Journal of the Portuguese Society of Anesthesiology, 2019)
Background: Pediatric scoliosis surgery, performed to improve quality of life and stop progression of the disease, has significant multifactorial blood loss and consequent consumption of blood products. A multidisciplinary protocol was implemented to standardize perioperative care and reduce blood product requirements. Material and Methods: An effectiveness evaluation, with contemporary (protocol “P”; 2016) and historical (pre-protocol “PP”; 2012-2014) cohorts was performed, using a systematic sample of patients aged 2-18 years-old, operated on more than 3 vertebral levels. Results: Sixty-three patients were recruited: 33 in the PP group and 30 in the P group. Both groups had similar age and weight (median 15 years old and 45 kg), males were more frequent in the group P (PP 12 vs P 33%). In the P group, the number of patients requiring concentrated erythrocyte unit intraoperative tended to be lower (PP 67% vs P 50%, p = 0.097), more patients received fibrinogen (PP 12% vs P 33%, p = 0.026) and the amount of fresh frozen plasma transfused tended to be higher (PP 8.6 vs P 13.3 mL/kg, p = 0.091). No statistically significant differences were found on the blood loss. Pre-operatory haemoglobin tended to be higher in the P group (PP 12.9 vs 13.5 g/ dL, p = 0.079) and the perioperative evolution of haemoglobin levels was different between groups, the haemoglobin level was an average of 0.45 g/dL higher in the protocol group (p = 0.023). Conclusion: Multidisciplinary patient blood management protocols may reduce the proportion of patients requiring blood transfusion.